PEMANFAATAN KAIN ATAU HANDUK BEKAS SEBAGAI MEDIA PENANAMAN BERBENTUK POT DI DESA SAWOTRATAP, KECAMATAN GEDANGAN, KABUPATEN SIDOARJO - Juliani Pudjowati; Rendy Bima Samudra; Rizal Wildan Putra; Benny Saputra; Fajar Yanuarko; Nur Indah Anjarwati; Rosa Khurrotin; Ida Bagus Gede Adyaguhyaka; Fathur Putra Meinando; Desy Delima Sah; Rahmadhani Setyo Budiono; Ika Ayu Wildaningtias; Ardhimas Zulkarnain Samsa; Retno Ayu W.; Fakhriza Fernanda; Sunaring Nizafatmala Firdhausa (Batara Wisnu : Indonesian Journal of Community Services, 2021)
This service is carried out for the community because many used cloth or towels are underutilized, so innovations are needed so that these used clothes or towels have a valuable meaning for the surrounding environment. One of the locations loth or towels is in the Sawotratap Village area, Gedangan District, Sidoarjo Regency, which coincides with RW 11 Hall; this activity introduced that used cor towels can be used used  The method used is training and discussion on the processing of used cloth or towels. The processing processes are: Preparing the mould, the immersion process, the drying process, the melting process, the painting process, the planting process. The conclusion is that with community service, training on making pots from used cloth or towels can reduce the negative impact of the presence of used cloth or towels, which can cause the accumulation of dry waste and empower the surrounding community that is tasked with preserving the surrounding environment. In addition to preserving the environment, it can also beautify the area around the house or village where you live